Optimasi fase gerak dan analisis kadar natrium benzoat pada beberapa sirup rasa jeruk dengan metode kromatografi cair kinerja tinggi (kckt) - Pulungan, Ainil Fithri; Santasa, Zhazha (Sasambo Journal of Pharmacy, 2024)
With the increasing growth of food and beverages in Indonesia, there has been an increase in the manufacture of soft drinks that use the preservative sodium benzoate, particularly in syrup. The concentration of sodium benzoate in beverages should be monitored, because excessive consumption can emerge various health problems. To obtain maximum analysis results, mobile phase optimization is first carried out, which aims to obtain the optimal type of eluent from several types of mobile phase, then proceed with adjusting the sodium benzoate content in the orange-flavored syrup using the HPLC method to establish whether it fits the standards in line with the BPOM Regulation No. 11 of 2019. After optimizing the mobile phase, the most optimal mobile phase is Methanol Pro HPLC: Aquabidestilata (70:30), because in this comparison the chromatogram gives the best result the peak shape is symmetrical, tailing factor is less than 2 and the retention time is less than 10 minutesBased on the findings of the third sample research, the sodium benzoate content in orange-flavored syrup meets the requirements of BPOM Regulation No. 11 of 2019, namely 600 mg/kg.